Respuesta :

Answer:

2

Step-by-step explanation:

[tex]\frac{(3*2)^4*3^{-3}}{2^3*3}[/tex]

we start simplifying by removing the parenthesis

Multiply the exponents inside the the parenthesis

3^4  * 2^4

[tex]\frac{3^4*2^4*3^{-3}}{2^3*3}[/tex]

Now we apply exponential property

a^m * a^n = a^ (m+n)

3^4 * 3^-3 = 3^ (4-3) = 3^1

3 or 3^1  are same

[tex]\frac{3^1*2^4}{2^3*3^1}[/tex]

3^1 at the top and bottom so we cancel it out

\frac{2^4}{2^3}

we apply log property . a^m / a^n = a^m-n

Now subtract the exponents

2^(4-3) = 2^1 = 2